(untitled) (Journal of Special Education and Rehabilitation, 2013)
The Master’s thesis is presented on 129 pages. The paper contains the following sections: introduction, theoretical approach to the problem of the research, research methodology, analysis of the results, discussion, conclusions, proposed measures, literature and articles. The introduction emphasizes the relationship between siblings as one of the basic interpersonal relationships among humans. If a family has an autistic member, some implications on the family and its functioning might arise, as well as on the relationship between the siblings.The presence of a child with autism alters the traditional role of a brother / sister in the family. Negative effects that may occur in the quality of the relationship between siblings,caused by having a child with autism in the family are: increased level of conflict, bitterness, resentment, loneliness, guilt, fear and reduced potential for conflict with peers outside the home. Of course, positive effects may also arise in the relationship between siblings in the family, such as: increased tolerance for diversity of others, kindness to others, increased levels of empathy, heightened sense of responsibility and maturity, a sense of happiness and well oriented view of life. The primary goal of the Master’s thesis is to explore the quality of the relationships between siblings in families that have an autistic child as well as to compare the quality of the brother – sister relationships in such families with the quality of the same relationship in a control group. By comparing the two groups, to determine the level and the character of the expected and perceived characteristics of the relationships between the children in families that have a child with autism (by their parents), and also to determine the level and the character of the expected and perceived characteristics of the relationships between the children in the families of the control group, i.e. the parents of neurotypical children (by those respective parents also). The theoretical basis gives explanation of the term and the definition of autism with emphasis on the prevalence, causes, clinical characteristics and the treatment. A significant segment of the theoretical basis are the quality of the relationship between siblings in the family, the autism and the effect on the relationship between siblings, the family and the disability, the perceptions of parents about the relationship between their children and the social support. The research part represents the subject of the research, the purpose and the nature of the research questions, the research hypotheses, the sample and the frame, the methods, the techniques and the instruments of the research. In the research, a sample of 132 respondents is provided, 66 of which are members of families that care for a child with autism, 66 are members of the control group families, i.e. families of neurotypical children. Data were gathered with the help of three questionnaires, processed by standard statistical software SPSS – 21 for Windows XP, by applying Mann – Whitney U and Wilcoxon W tests, for the independent and correlated samples, respectively. For the statistically significant difference we used the difference that has a significance level of p < 0. 05. In the section relating to the analysis and the interpretation of the results, based on the conducted research, the analysis has shown that in relation to the positive characteristics of the quality of the relationships between siblings, there is no statistically significant difference in the category of “empathy”, “affections” and “boundary maintenance”, apart from the category of “similar interests”, which is higher among the siblings from the control group (M = 27,72,SD = 7,68) and studied group(M = 19,15,SD = 4,48),(p < 0.01). While in relation to the negative characteristics of the relationships between siblings, there is a statistical significant difference only in the level of “coercion” in that relationships, which is lower in families that have children with autism (M = 10,10, SD = 1,58)and (M = 12,34,SD = 2,28), (p < 0.01) of the control group. In the level of “rivalry” and “hostility” between the control and studied group differences were not found.Furthermore, in relation to the expected and perceived negative characteristics by the parents we found that there is a statistically significant difference in the level of the “perceived rivalry” which is lower with the parents of children with autism with (M = 5,55, SD = 2,45) and (M = 7,15, SD = 2,12)of the control group(p < 0.01).There is no difference in the level of expected rivalry and expected and perceived hostility perceived by parents in both groups. Also, while exploring the expected and perceivedpositive characteristics by the parents, the level of “perceived closeness” in the relationships between siblings is higher in families from the control group (M = 48,45, SD = 5,93)and (M = 42,56, SD = 7,89) of the studied group, (p < 0.01). There is also a difference in the “expected closeness”that is higher in the control group with (M=51,70, SD=5,50) and (M=46,33, SD=8,49)of the studied group,(p < 0.01). There are certain differences in the quality of the relationships between siblings, depending on whether it is a matter of a family that has a child with autism, or a family from, conditionally speaking, the regular population. However, we believe that those differences are not necessarily carrying a negative connotation. An action for raising the public awareness in relation to autism is necessary, which will contribute to the decrease of the stigma that the families perceive.